Ultrastructure of GABA- and Tachykinin-Immunoreactive Neurons in the Lower Division of the Central Body of the Desert Locust - Homberg, Uwe; Müller, Monika (Frontiers in Behavioral Neuroscience, 2016)
The central complex, a group of neuropils spanning the midline of the insect brain, plays a key role in spatial orientation and navigation. In the desert locust and other species, many neurons of the central complex are sensitive to the oscillation plane of polarized light above the animal and are likely involved in the coding of compass directions derived from the polarization pattern of the sky. Polarized light signals enter the locust central complex primarily through two types of γ-aminobutyric acid (GABA)-immunoreactive tangential neurons, termed TL2 and TL3 that innervate specific layers of the lower division of the central body (CBL). Candidate postsynaptic partners are columnar neurons (CL1) connecting the CBL to the protocerebral bridge (PB). Subsets of CL1 neurons are immunoreactive to antisera against locustatachykinin (LomTK). To better understand the synaptic connectivities of tangential and columnar neurons in the CBL, we studied its ultrastructural organization in the desert locust, both with conventional electron microscopy and in preparations immunolabeled for GABA or LomTK. Neuronal profiles in the CBL were rich in mitochondria and vesicles. Three types of vesicles were distinguished: small clear vesicles with diameters of 20–40 nm, dark dense-core vesicles (diameter 70–120 nm), and granular dense-core vesicles (diameter 70–80 nm). Neurons were connected via divergent dyads and, less frequently, through convergent dyads. GABA-immunoreactive neurons contained small clear vesicles and small numbers of dark dense core vesicles. They had both pre- and postsynaptic contacts but output synapses were observed more frequently than input synapses. LomTK immunostaining was concentrated on large granular vesicles; neurons had pre- and postsynaptic connections often with neurons assumed to be GABAergic. The data suggest that GABA-immunoreactive tangential neurons provide signals to postsynaptic neurons in the CBL, including LomTK-immunolabeled CL1 neurons, but in addition also receive input from LomTK-labeled neurons. Both types of neuron are additionally involved in local circuits with other constituents of the CBL.